Sparkol Learning Media: Is it Effective to Improve Students’ Mathematical Understanding? - Yani, Meri; Shahril, Sulthan; Putra, Rizki Wahyu Yunian; Simatupang, Adolf T (Indonesian Journal of Science and Mathematics Education, 2020)
The aims of this study are to find out the view of the validator on learning Sparkol media, to find out the students’ views on learning the Sparkol media, to know the effectiveness of learning by using Sparkol learning media. This research and development used the ADDIE research model. Media development based on Sparkol Videoscribe using Research and Development with Addie model which has 5 stages: Analysis, Design, Development, Implementation, and Evaluation. Student responses to the feasibility of learning media with Sparkol show that this media is feasible and attractive to students. The effectiveness of learning using Sparkol Videoscribe-based mathematics learning media was tested in the range , this result shows that the category is quite effective.